Returns to agricultural public spending in Africa south of the Sahara - Benin, Samuel (International Food Policy Research Institute, 2015)
Using data on 34 countries in Africa south of the Sahara (SSA) from 1980 to 2012, this paper assesses the returns to public spending in the agricultural sector, considering expenditures on agriculture as a whole versus expenditures on agricultural research. First, an aggregate production function is estimated using a fixed-effects, instrumental variables estimator to address potential endogeneity of agricultural expenditure and to obtain elasticities of land productivity with respect to total agricultural expenditure and agricultural research expenditure. Different model specifications are used to test the sensitivity of the results to different assumptions. The estimated elasticities are then used to estimate the rate of return to expenditure in different countries and groups of countries. The elasticity of land productivity with respect to total agricultural expenditure per hectare is estimated at 0.04, and elasticity with respect to agricultural research expenditure per hectare is estimated to be higher at 0.09. The aggregate returns to total agricultural expenditure and agricultural research expenditure in SSA are estimated at 11 percent and 93 percent, respectively. Comparative analysis of the estimates with those of previous studies, as well as across different countries and different groups of countries, is undertaken. Then implications are discussed for maintaining the high returns to agricultural research expenditure and for further studies on the low return to total agricultural expenditure, including more disaggregated analysis of expenditure on other functions besides research to better inform prioritization of agricultural expenditure.